Career Development of Sexual Minority Men Living With HIV. (October 2018) - Dispenza, Franco; Murphy, Thomas M.; Zeligman, Melissa
HIV is a diagnosis that disproportionally affects sexual minority (e.g., gay, bisexual, and queer) men living in the United States. Expansive treatment options have allowed those living with HIV to live longer life spans, indicating that sexual minority men living with HIV are remaining engaged in the workforce longer. Yet, there remains a dearth of literature exploring the career trajectories of this specific population. This qualitative study aimed to understand what factors keep sexual minority men ( N = 10) living with HIV actively engaged in the workforce. Through in-depth individual interviews, a central category of psychosocial motility was constructed. Three subsequent categories were also constructed: affirmative support systems, intrinsic and extrinsic incentives, and intrapersonal endowments . Findings are discussed, along with implications for practice, limitations, and future research.